Microstructure and Mechanical Properties of Li2Si2O5 Whisker-Reinforced Glass-Ceramics - Yan, Jingyu; Liu, Xiaoming; Wu, Xiuping; Wu, Xiao; Zhang, Yanjie; Li, Bing (Frontiers in Materials, 2022)
Lithium disilicate (Li2Si2O5) glass-ceramics are an ideal material for dental restoration; however, their intrinsic brittleness and low defect tolerance limit the scope of their clinical applications. In this study, Li2Si2O5 whiskers were creatively synthesized via a mild-condition hydrothermal reaction. Self-reinforced Li2Si2O5 glass-ceramics were sintered by introducing the Li2Si2O5 whiskers, and their effects on phase, microstructure, and mechanical properties were systematically studied. The crystal-growth and toughening mechanisms were also discussed. The results showed that the Li2Si2O5 whiskers played an important role in inducing crystallization, and improving the microstructure and properties of the glass-ceramics. With increasing amounts of Li2Si2O5 whiskers, the crystallinities increased slightly, and the average crystal size also increased. The microstructure was composed of crystals of bimodal size distributions, in which some large, rod-like Li2Si2O5 crystals epitaxially grew along with the whiskers, and small crystals directly crystallized from the parent glass-ceramic powders. The Li2Si2O5 glass-ceramics exhibited high flexural strength (389.5±11.77MPa, LDW3), and fracture toughness (3.46±0.10 MPa·m1/2, LDW5). The improved properties were attributed mainly to crack deflection and bridge-toughening mechanisms.